2010
DOI: 10.1021/ic1015109
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic, Electrochemical, High-Pressure Kinetic, and Mechanistic Studies of the Formation of Oxo FeIV−TAML Species in Water

Abstract: Stopped-flow kinetic studies of the oxidation of Fe(III)-TAML catalysts, [ F e{1,2-X(2)C(6)H(2)-4,5-( NCOCMe(2) NCO)(2)CMe(2)}(OH(2))](-) (1), by t-BuOOH and H(2)O(2) in water affording Fe(IV) species has helped to clarify the mechanism of the interaction of 1 with primary oxidants. The data collected for substituted Fe(III)-TAMLs at pH 6.0-13.8 and 17-45 °C has confirmed that the reaction is first order both in 1 and in peroxides. Bell-shaped pH profiles of the effective second-order rate constants k(I) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
(96 reference statements)
4
39
0
Order By: Relevance
“…61 This behavior of the Fe(III)-OH / Fe(IV)=O molecular complexes is therefore in good agreement with the proposed first water oxidation step on hematite electrodes. In addition, it was shown that an intermediate Fe(IV)=O complex has a broad absorption spectrum centered at 820 nm.…”
Section: Resultssupporting
confidence: 86%
“…61 This behavior of the Fe(III)-OH / Fe(IV)=O molecular complexes is therefore in good agreement with the proposed first water oxidation step on hematite electrodes. In addition, it was shown that an intermediate Fe(IV)=O complex has a broad absorption spectrum centered at 820 nm.…”
Section: Resultssupporting
confidence: 86%
“…The formation of Fe V and Fe IV species from 1 and either H 2 O 2 or t BuOOH has been discussed in detail in a recent mechanistic publication. 19 It is worth noting here that m-chloroperbenzoic acid converts 1b into the monomeric iron(V)oxo species in organic nitriles 20 which performs a clean and very fast 2e oxidation of thioanisoles. 21 Mossbauer and EXAFS spectroscopies support the case that 1a reacts with t BuOOH in water to give Fe IV observable species, 22 a 1e oxidation performed by a 2-electron oxidant with the likely intermediacy of an iron(V)oxo complex that comproportionates rapidly with additional 1a.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Stopped-flow kinetic measurements were carried out using a two-syringe BioKine32 SFM-20 model (BioLogic Science Instruments) at 25 °C. Technical details are summarized elsewhere [14]. Products of the oxidation of thioanisoles were analyzed by high performance liquid chromatography (HPLC) using a Varian C18 Omnispher column with acetonitrile and water as eluting solvents, as well as by gas chromatography -mass spectrometer (GC-MS) using a ThermoDSQ instrument.…”
Section: Methodsmentioning
confidence: 99%
“…In 2008 we reported that TAML complex 1 (chart 1) is transformed by t BuOOH in water into iron(IV) derivatives 2 and/or 3 depending on reaction conditions [12,13]. Later, the kinetics and mechanism of this transformation were explored in detail in collaboration with Professor Rudi van Eldik, to whom this issue is devoted [14]. Our investigations of the reactivity of Fe V and Fe IV complexes derived from TAMLs, which were performed at -40 °C in MeCN, revealed that both forms oxidize thioanisoles, though Fe V is by several orders of magnitude more reactive than Fe IV [15].…”
Section: Introductionmentioning
confidence: 99%